RANCANGAN SISTEM INFORMASI UKM STMIK KOMPUTAMA MAJENANG BERBASIS WEB - Diky Setiawan; miftahul Khoeri, Amarulloh; Fajar Syafani, Henky; Ristianingsih; bambang Sumantri, R Bagus (Jurnal Teknologi dan Bisnis, 2021)
Student activity unit (UKM) STMIK KOMPUTAMA MAJENANG is a student organization outside the classroom that is engaged in various fields, such as Wanacetta, Racana Pramuka, Sports, Web Programing, etc. Information dissemination to UKM itself is not yet fully effective, it needs information media to publish information related to UKM. Among other things, to find out information related to the field of UKM, participate in UKM, and can also participate in managing UKM management. Therefore, this system was created to help students and lecturers to get information about UKM and facilitate data management that can be accessed via a Web browser. This information system was created using the Waterfall method, Boostrap Framework, Html, Css, PHP programming language and MYSQL database. This system is still in the form of a design or prototype that has not been fully completed, it is still in the development process. So that there is still a need for further processes in completing the Prototype of this System both from Design, Content of the website, Testing, and also maintenance.